2019
DOI: 10.1177/0363546519888647
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Elbow Magnetic Resonance Imaging Abnormalities in Little League Baseball Players Are Common: A 3-Year Longitudinal Evaluation

Abstract: Background: Prior studies have revealed magnetic resonance imaging (MRI) evidence of elbow pathology in single-season evaluation of competitive youth baseball players. The natural history of these findings and risk factors for progression have not been reported. Purpose: To characterize the natural history of bilateral elbow MRI findings in a 3-year longitudinal study and to correlate abnormalities with prior MRI findings, throwing history, playing status, and physical examination. Study Design: Cohort study; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…( 65 ) showed that the expression of integrins in tendon did not correlate with the increase of loading dose, suggesting an overuse-induced ECM damage that regulates mechanosensitivity. Our findings model the structural and mechanical changes similar to those occurring in pediatric apophyseal pathologies and in young athletes ( 66 , 67 ). This study provides the first small animal model of pediatric apophyseal pathologies and can be leveraged for future systematic examination of mechanisms of injury and repair in the growing skeleton.…”
Section: Discussionsupporting
confidence: 71%
“…( 65 ) showed that the expression of integrins in tendon did not correlate with the increase of loading dose, suggesting an overuse-induced ECM damage that regulates mechanosensitivity. Our findings model the structural and mechanical changes similar to those occurring in pediatric apophyseal pathologies and in young athletes ( 66 , 67 ). This study provides the first small animal model of pediatric apophyseal pathologies and can be leveraged for future systematic examination of mechanisms of injury and repair in the growing skeleton.…”
Section: Discussionsupporting
confidence: 71%
“…However, the authors did not find significant correlations between progressive abnormal MRI findings and throwing history (including years of play, primary position of play, months of play per year, and physical examination findings, such as shoulder ROM, shoulder strength, and shoulder and elbow instability). Holt et al 11 also reported that year-round play was a significant predictor of positive MRI findings at 3 years; however, the MRI findings included both new lesions and pre-existing lesions, which do not reflect the progression of abnormal MRI findings. Thus, it remains unclear which factors influence the progression of elbow abnormalities on US or MRI.…”
Section: Discussionmentioning
confidence: 98%
“…Holt et al 11 prospectively evaluated the progression of MRI-detected elbow abnormalities in 26 Little League players (aged 12 to 15 years) to determine whether pitchers, catchers, or year-round players (defined as ≥ 8 months per year) with continued play would have more severe and progressive elbow abnormalities on MRI at the 3-year follow-up. The authors found that 57.7% of players displayed dominant elbow MRI pathology at the 3-year follow-up, with 80.0% of these patients developing new or progressive abnormal findings, compared to the findings of prior MRI studies.…”
Section: Discussionmentioning
confidence: 99%
“…This injury occurs almost exclusively in throwing athletes such as baseball players, during the cocking phases of throwing when valgus stress on the medial elbow is maximal [ 8 , 10 , 11 ]. Approximately 20–50% of youth baseball players report elbow pain, and recent radiographic assessments of the medial elbow using ultrasonography and MRI have reported medial epicondyle abnormalities ranging from 10 to 50% on the throwing side [ 2 , 3 , 30 •, 31 36 ].…”
Section: Elbowmentioning
confidence: 99%